Implementasi Pembelajaran Klasikal Dalam Pendidikan Karakter Anak Pada Kelompok Bermain Al-Fawwaz Kota Tasikmalaya - Purwati Purwati; Nuruzahra Luthfillah; Taopik Rahman (UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to instill character education in early childhood through a classical learning model. This character education is very important considering that what children get from an early age can stick with them until they grow up. The method used in this research is field study or observation and literature study, by analyzing the findings from observations in the field and then linking them to theories related to this research study. The results of the study explain that the classical learning model is still very effective for children's learning, especially in habituation activities for instilling character in children. The process of implementing it at Kober Al-Fawwaz is through disciplinary habituation in children, forming religious character, forming active learning strategies for children, and building good role models for children. Besides that, the character values that are instilled in children are aspects of independence, discipline, environmental care, social care, responsibility, and creativity in children.